“Treat us as a person”: A narrative inquiry of experiences and expectations of interactions with pharmacists and pharmacy staff among people who are transgender - Swapna Chaudhary; Robin Ray; Beverley D. Glass (Exploratory Research in Clinical and Social Pharmacy, 2022)
Background: Despite the increased visibility of transgender and gender diverse (TGD) people, little is known about their interactions with pharmacists and pharmacy staff while accessing care from the pharmacies. Objectives: The objective of this study was to explore the experiences and expectations of the TGD people regarding their interactions with pharmacists and pharmacy staff in Queensland, Australia. Methods: This study is situated in a transformative paradigm and utilized narrative inquiry to conduct semi-structured interviews with TGD participants. An interview guide based on the relevant literature and the constructs of the Theoretical Framework of Accessibility was developed. Purposive and snowball sampling was used to recruit people who identified as TGD and had previously visited pharmacies to access care. Depending on participants' preferences, interviews were conducted face-to-face or via phone or Zoom application. Interviews were recorded, transcribed, and organized in chronological stories. Data were analyzed to derive themes from the participant stories. Results: A total of 22 participants (transwomen = 11, transmen = 8, non-binary trans masculine = 3) were interviewed. Two major themes were identified, (1) Challenges of accessing care from the pharmacy and (2) Making the most of the interactions between TGD people and pharmacists. Major challenges of accessing care from pharmacies included anticipated anxiety of accessing care, healthcare system constraints, compromised privacy and confidentiality at the pharmacy, and being challenged about their gender. Many avoided interacting with pharmacists and staff or kept their interactions minimal. Participants recognized that pharmacists play a meaningful role in TGD health and provided insights about how pharmacists can improve care provision to TGD people. Conclusion: Cultural and pharmacotherapeutic education in transgender health are crucial for Australian pharmacists and staff to provide inclusive, respectful, and person-centered care to TGD people.